The Effect of Work Engagement, Work-Life Balance, and Work Overload on Employee Productivity: The Role of Job Satisfaction as A Mediating Variable at BRI Employees in Bandung City - Nugraha, Bayu Wiguna; Rukhviyanti, Novi (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the relationship between job satisfaction as a mediating variable and banking employee work productivity on Work Engagement, work-life balance, and work Overload. This research was conducted at Bank BRI Bandung City and is included in the quantitative descriptive research category. This research used a random sampling approach by selecting 100 BRI Bank employees in Bandung City as samples. This research uses Partial Least Squares (PLS), the research results show that Work Engagement and Work-Life Balance have a significant influence on the Work Productivity of BRI Bank Employees in Bandung City, indicating that employees are more involved in their work and who have balanced between work life and good individuals tend to be more productive. Meanwhile, Work Engagement shows a positive but not significant effect on employee work productivity, Work-Life Balance affects employee work productivity. Work Overload shows no effect on employee work productivity, which indicates that excessive workload does not directly increase the work productivity of BRI Bank employees. in Bandung City. In addition, this research confirms that Job Satisfaction has an important mediating role in the relationship between workplace characteristics (Work Engagement, Work-Life Balance) and Employee Work Productivity. Thus, efforts to increase employee job satisfaction can strengthen the positive impact of Work Engagement and Work-Life Balance on productivity.